RNA Metabolism in Mitochondria (Nucleic Acids and Molecular Biology,, 2018)
This volume focuses on mitochondrial RNA metabolism, emphasizing recent discoveries and technological advances in this fast moving area that increase our understanding of mitochondrial gene function. Topics addressed include the interplay of mitochondria with the nucleus and cytosol, structure-function connections, and relevance to human disease. Mitochondria are the powerhouses of the cell, and a great deal is known about mitochondrial energy metabolism. Less well known is the plethora of amazing mechanisms that have evolved to control expression of mitochondrial genomes. Several RNA processes and machineries in protozoa, plants, flies and humans are discussed, including: transcription and RNA polymerase mechanism; tRNA processing of 5' and 3' ends; mRNA maturation by nucleotide insertion/deletion editing and by RNA splicing; mRNA stability; and RNA import. Specialized factors and ribonucleoproteins (RNPs) examined include pentatricopeptide repeat (PPR) proteins, RNase P, polymerases, helicases, nucleases, editing and repair enzymes. Remarkable features of these processes and factors are either not found outside mitochondria, differ substantially among eukaryotic lineages, or are unique in biology. .